Step-by-step explanation:
Given equations:
y = x² + 3x - 29 ------ (i)
y = 2x - 9 ---------------- (ii)
Now to solve this problem, we must determine the value of x and y;
Equate equations 1 and 2;
x² + 3x - 29 = 2x - 9
x² + 3x - 2x - 29 + 9 = 0
x² + x - 20 = 0
x² + 5x - 4x - 20 = 0
x(x + 5 ) - 4(x + 5) = 0
(x - 4) (x+ 5) = 0
x - 4 = 0 or x + 5 = 0
x = 4 or x = -5;
So; solve for y now;
y = 2x - 9
input x = 4 or x = -5;
y = 2(4) - 9 or y = 2(-5) - 9
y = -1 or y = -19
Answer:
The quotient ix 3x - 1.
Explanation:
Use Long division:
3x - 1 <------------quotient.
---------------------
x + 3) 3x^2 + 8x + 3
3x^2 + 9x
-------------
-x + 3
-x - 3
------
6 <---------remainder.
Like terms are when numbers with and without variables can be combined. ex: 4x+6-8x+=32
you would first combine 4x and -8x because they are the same.